AnÃ¡lisis De La Fuerza Explosiva En El Golpe De BalÃ³n Con El Pie En Los Futbolistas CategorÃa Senior De La Universidad Nacional De Chimborazo â€“ Ecuador. Estudio De Caso: Test De PrecisiÃ³n De Golpe De BalÃ³n - Moreno, Orlando David MazÃ³n; Lobato, Jorge Giovanny Tocto; Machado, RamÃ³n Fernando Bayas (European Scientific Journal, ESJ, 2017)
The objective of the present study is to research the incidence of explosive strength on the ball kick of senior category soccer players from the â€œUniversidad Nacional de Chimborazoâ€. The study was carried out through the application of a comprehensive training program to improve explosive strenght and ball kick for 8 weeks. In this study, 50 soccer players were also evaluated. The age, body weight (kg), height (cm), and body mass index were also evaluated. The pre-post ball kick precision test was applied as well. The soccer sketch 2.5.0 program was used for the preparation of the training sessions, while the SPSS statistical package was used for the results tabulation. The results obtained are as follows: average age of 21.82, average body mass index 26.72 (kg/m2). An average of 2.38 goals was obtained in the pre-test of ball precision, while an average of 3.64 goals was obtained in the post-test whit a level of significance of 0.001. In conclusion, the application of training sessions based on comprehensive exercises of explosive strength and ball kick are very important in improving the sports performance of the soccer players.